Le rôle d’Adelaide Ristori dans la formation de la scène nationale grecque - Altouva, Alexia (Drammaturgia, 2023)
Adelaide Ristori travelled to Athens in 1865, during her tour of the Eastern Mediterranean, which included major economic and cultural centres in the region. She was the first major actress of the time to travel to the Greek capital to present part of her repertoire. Her theatrical presence, her production on stage as well as her personality as a whole marked the theatre audience, the intellectual elite, even the Athenian bourgeoisie who were lucky enough to admire the great artist’s dramatic art. Being an eminent personality of European theatre, she had a profound influence on the style of performances, from an aesthetic point of view, but also on public opinion regarding dramatic art in general and especially the presence of women on the theatre stage. The presentation will focus on the different areas that she marked in the most pregnant and effective way, contributing to the formation of the Greek national theatre. The data presented here comes from primary research and is based on scientific studies, press of the time and relevant bibliography.